Предмет: Алгебра,
автор: troyan2005
ОЧЕНЬ СРОЧНО. ДАЮ 35 Б.
Приложения:
Ответы
Автор ответа:
1
а) (х+3)(х+3) / (х-3)(х+3) - (х-3)(х-3) / (х-3)(х+3) = 12х / (х-3)(х+3)
(х+3)(х+3) - (х-3)(х-3) = 12х
х^2 + 6x +9 - (х^2 - 6x +9) = 12x
х^2 + 6x +9 - х^2 + 6x -9 = 12x откуда 12х=12х
б) 11 / (х+2)(х+2) * (х+2)/х = 11 / (х^2 + 2х)
11 / (х+2) * 1/х = 11 / (х^2 + 2х)
11 / (х^2 + 2х) = 11 / (х^2 + 2х)
Похожие вопросы
Предмет: Биология,
автор: 5355754
Предмет: Русский язык,
автор: coffeesss
Предмет: Английский язык,
автор: zabanyan1raz
Предмет: Музыка,
автор: Аноним
Предмет: Математика,
автор: KseniyaDomaeva